Linguistic rulings in the Quranic readings and the effect of apprenticeship therein - Jabr, Muhammad Shamkhi (Thi Qar Arts Journal, 2023)
There is no doubt that the subject of Quranic recitations is one of the topics that have attracted the attention of researchers, past and present, so this research came to show some of these linguistic rulings and the impact of apprenticeship in them. Whether this difference is on the phonetic, morphological or grammatical level, the research came on an introduction and two topics. The first topic was entitled Grammatical rulings in the Qur’anic readings and the effect of apprenticeship in them. In terms of phonetic and morphological rulings in the Qur’anic readings and the impact of apprenticeship therein, it is in two requirements, the first in the two hamzas combined in one word, and the second in the confluence of the dwellers, and the research ended with a conclusion in which the most important results were shown.